Design as Advocacy: Using a Human-Centered Approach to Investigate the Needs of Vulnerable Populations - Rose, Emma J. (Journal of technical writing and communication)
Human-centered design expands the context and reach of the work of technical communicators and provides an opportunity to investigate and advocate for the needs of vulnerable populations. This article summarizes and contributes to the conversation about social justice occurring in both technical communication and design. Using a variety of qualitative methods as a type of design ethnography, this article shares findings from a study that investigated the experiences of homeless bus riders. The study findings provide an opportunity to examine the design of information and communication technologies and changes to policies that impact vulnerable populations. The article discusses the implications of an advocacy perspective for technical communicators practicing human-centered design and their role and opportunity to bring about socially responsible design.